2018
DOI: 10.1186/s12891-018-2097-4
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular cup orientation and postoperative leg length discrepancy in patients undergoing elective total hip arthroplasty via a direct anterior and anterolateral approaches

Abstract: BackgroundTotal hip arthroplasty (THA) is considered a successful surgical procedure. It can be performed by several surgical approaches. Although the posterior and anterolateral approaches are the most common, there has been increased interest in the direct anterior approach. The goal of the present study is to compare postoperative leg length discrepancy and acetabular cup orientation among patients who underwent total hip arthroplasty through a direct anterior (DAA) and anterolateral (ALA) approaches.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, it is still controversial whether there is a difference in leg length discrepancy between patients after THA using the DAA and LA approaches. Although the study of Debi et al 54 . showed a good outcome in LLD values in patients who underwent THA by the DAA compared to the anterolateral approach (ALA), most authors stated that both DAA and ALA showed similar results in postoperative leg length control 55, 56 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still controversial whether there is a difference in leg length discrepancy between patients after THA using the DAA and LA approaches. Although the study of Debi et al 54 . showed a good outcome in LLD values in patients who underwent THA by the DAA compared to the anterolateral approach (ALA), most authors stated that both DAA and ALA showed similar results in postoperative leg length control 55, 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Malposition of the acetabular cup is associated with complications such as impingement, recurrent dislocation, increased ischial osteolysis and wear of prosthetic components [36][37][38]. Few studies have evaluated acetabular cup placement depending on the surgical approach [29,[39][40][41]. MIS techniques arose with the simultaneous effort to reduce periarticular tissue damage and achieve good clinicalradiographic results, the latter at least overlapping with those obtained with traditional surgical approaches [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Both the PLA and DAA to THA have been used successfully, but the surgical approach remains a topic of contention among arthroplasty surgeons. Literature has suggested that the DAA provides better outcomes of postoperative pain, LOS, functional recovery, and patient-reported outcome measures [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. However, there are studies suggesting that this approach offers no benefit compared with other approaches for THA and potential increased risk of periprosthetic fracture or early reoperation [ 3 , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed benefits of DAA THA have been described extensively including the following: decreased visual analog scale (VAS) pain scores in the immediate postoperative period, reduced hospital length of stay (LOS), greater likelihood of home discharge, improved acute patient-reported outcome scores, lower creatine kinase levels postoperatively, and more accurate acetabular cup placement [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Furthermore, more rapid functional recovery after the DAA is perhaps the most cited advantage of the DAA.…”
Section: Introductionmentioning
confidence: 99%